2021
DOI: 10.1038/s41545-021-00111-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between general health knowledge and sanitation improvements: evidence from rural China

Abstract: A lack of access to sanitation not only has negative effects on the environment but also results in increased prevalence of disease and adversely affects health outcomes. This paper uses data from a survey in Liaoning Province in China to examine the relationship between general health knowledge and improved sanitation facility access. It also explores the effects of work experience and government subsidies on toilet renovation. Using Logit Regression and Duration Analysis, our results show that general health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The research hypothesis H3 confirmed that policy cognition has a significant impact on rural residents’ participation in rural health governance, which is consistent with the research results of Zheng, W. [ 63 ] and Chen, F. [ 64 ] et al The improvement of rural residents’ cognition of policy programs and improvement projects can prompt them to engage in more reliable environmental governance behaviors [ 65 ]. The long-term increase in the level of economic income has allowed rural residents to get rid of their worries about basic living needs and begin to focus on spiritual satisfaction and improving their quality of life [ 66 ]. The cognition of the individual health part of policy cognition can promote individuals to choose hygienic individual behaviors and take actions that are beneficial to the rural public environment, such as participating in a garbage clean-up in rural areas [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research hypothesis H3 confirmed that policy cognition has a significant impact on rural residents’ participation in rural health governance, which is consistent with the research results of Zheng, W. [ 63 ] and Chen, F. [ 64 ] et al The improvement of rural residents’ cognition of policy programs and improvement projects can prompt them to engage in more reliable environmental governance behaviors [ 65 ]. The long-term increase in the level of economic income has allowed rural residents to get rid of their worries about basic living needs and begin to focus on spiritual satisfaction and improving their quality of life [ 66 ]. The cognition of the individual health part of policy cognition can promote individuals to choose hygienic individual behaviors and take actions that are beneficial to the rural public environment, such as participating in a garbage clean-up in rural areas [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The regressions also included a series of control variables used in prior studies on both flush toilet use and household expenditure (Akpalu & Normanyo, 2017; Callander et al, 2019; Duflo et al, 2015; Huang et al, 2021; Kapri & Jha, 2020; Stopnitzky, 2017; Villalobos Dintrans, 2018). These included age, gender, education, household size, dependency ratio, farm size, car ownership, health insurance, water pollution perception, housing congestion, proximity to government and regional dummies (i.e., eastern, central and western China).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the effects of flush toilet use on household expenditure have been overlooked in the literature. Existing studies (Capuno et al, 2015; Duflo et al, 2015; Huang et al, 2021) have proven that flush toilet use significantly improves rural sanitation and mitigates infectious diseases, which could be promising to reduce rural residents' health expenditure. However, this association between them remains a research gap warranted to fulfil.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have noticed that successful implementation of the RTR in China is hindered by several factors, mainly geographic and technological constraints ( 17 , 18 ), and funding barriers ( 9 , 19 , 20 ). From the cultural perspective, previous studies have focused on the life concept, sanitation knowledge, and religious beliefs that affect villagers' willingness to participate ( 21 , 22 ). And the positive willingness of local villagers to pay and participate will promote rural sanitation facilities ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%